Endowment Structures, Industrial Dynamics, and Economic Growth - Ju, Jiandong; Lin, Justin Yifu; Wang, Yong (2012)
This paper develops a dynamic general equilibrium model to explore industrial evolution and economic growth in a closed developing economy. The authors show that industries will endogenously upgrade toward the more capital-intensive ones as the capital endowment becomes more abundant. The model features a continuous inverse-V-shaped pattern of industrial evolution driven by capital accumulation: As the capital endowment reaches a certain threshold, a new industry appears, prospers, then declines and finally disappears. While the industry is declining, a more capital-intensive industry appears and booms, ad infinitum. Explicit solutions are obtained to fully characterize the whole dynamics of perpetual structural change and economic growth. Implications for industrial policies are discussed.